Calculus for biological scientists - OER project materials - Shriner, Jeff, author (Colorado State University. Libraries, 2024)
For interactive version and optimum user experience, please see: https://jshriner6.github.io/bio-calc1/root-1-2.html.
Functions as models -- The derivative -- Using the derivative -- Continuous-time dynamical systems.
This document contains a set of materials collected for the OER project funded by the Colorado OER Council Grant (AY 2021/22). The following materials are included: online and PDF versions of the textbook.
Original version 2022. Revised May 9, 2024.